2022
DOI: 10.1101/2022.09.07.507054
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low forces push the maturation of neural precursors into neurons

Abstract: Mechanical stimulation modulates neural development and neuronal activity. In a previous study, we proposed magnetic nano-pulling as a tool to generate active forces. By loading neural cells with magnetic nanoparticles (MNPs), a precise force vector is remotely generated through static magnetic fields. In the present study, human neural stem cells (NSCs) were subjected to a standard differentiation protocol, in the presence or absence of nano-pulling. Under mechanical stimulation, we found an increase in the l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 72 publications
7
2
0
Order By: Relevance
“…2C). This data on mitochondria in stretched ganglia are in line with previous finding on mice, human and chick isolated neurons (Lamoureux et al, 2010; De Vincentiis et al, 2023; Falconieri et al, 2023)…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…2C). This data on mitochondria in stretched ganglia are in line with previous finding on mice, human and chick isolated neurons (Lamoureux et al, 2010; De Vincentiis et al, 2023; Falconieri et al, 2023)…”
Section: Discussionsupporting
confidence: 93%
“…2C). This data on mitochondria in stretched ganglia are in line with previous finding on mice, human and chick isolated neurons (Lamoureux et al, 2010;De Vincentiis et al, 2023;Falconieri et al, 2023) Endoplasmic reticulum is another key component for the production of proteins required for axon regeneration. Our experimental data revealed a strong increase in ER cisternae in stretched samples compared to spontaneous regeneration (fig.…”
Section: Discussionsupporting
confidence: 91%
“…Apoptotic rate (% aCasp3 + cells/Total number of Hu-Nu + cells) was found to be very low (0.44±0.34 %) after 30 DPT ( Figure 5B ). Moreover, the apoptotic rate at DPT 30 was found to be in line with that one found for the same type of cells at DPT 7, reported in De Vincentiis, S. et al, 2023 , documenting that the cultures stabilize with time.…”
Section: Representative Resultssupporting
confidence: 87%
“…The neural stem cell graft into slices was maintained for 30 days after transplant and cells showed GFP expression for all the period in culture. The apoptotic rate of cells at day post-transplant (DPT) 30 was also found to be in line with respect to the apoptotic rate value observed at DPT 7 in the same cells ( De Vincentiis, S. et al, 2023 ). Cells seemed to engraft into the tissue environment and survived up to several weeks.…”
Section: Introductionsupporting
confidence: 75%
“…Arulmoli et al ( Arulmoli et al, 2015 ) found that statically stressed membranes increased the differentiation of neural stem cells and neural progenitor cells into oligodendrocytes. Magnetic manipulation, another technique to investigate the effect of stretching and resulting nano-pulling, promoted neural differentiation, axonal elongation, sprouting, and neuron maturation ( Vincentiis et al, 2022 ). In addition, Vincentiis et al ( Vincentiis et al, 2022 ) showed that the nano-pulling stimulation led to a reorganization of the neural network and remodelling at the level of synapse density, halving the required time for maturation of neural precursors into neurons.…”
Section: Mimicking the Brain Microenvironment In Vitromentioning
confidence: 99%